Correlation between microbial host factors and caries among older adults - Rakhi Mittal; Kai Soo Tan; Mun Loke Wong; Patrick Finbarr Allen (BMC, 2021)
Abstract Background There is little knowledge about factors which may affect oral health among older adults. The objective of this study was to determine the relationship between Streptococcus mutans (MS) and Lactobacilli (LB) counts and caries among older adults. Methods In this community-based observation study, 141 participants aged 60 years and above were recruited from the west district of Singapore. Alongside the clinical examination, saliva samples were collected to determine Streptococcus mutans (MS) and Lactobacilli (LB) counts, as well as to record salivary flow rate and buffering capacity of saliva. Results Of the 141 participants, 63.8% were female and 94.3% were of Chinese ethnicity. The mean DMFT was 11.08 (s.d. 8.27). 9.9% of participants had at least one decayed tooth, 52.5% had minimum one missing tooth and 86.5% had at least one filled tooth. 67.4% had MS counts of ≥ 105 while LB counts were ≥ 105 for 48.2%. 83.7% had normal salivary flow or hypersalivation (> = 1 mL/min), the buffering capacity of the saliva was alkaline in 61% of the participants. Multivariate analysis showed that participants who had high MS counts were less likely to have a DMFT < 12 [OR (95% CI), 0.29 (0.11-0.77)] whereas participants who had high LB counts were less likely to have a DMFT ≤ 14 [OR (95% CI), 0.45 (0.20-1.002)]. Conclusion Our study showed a positive correlation between MS and LB counts and caries experience in older adults. The mean DMFT was on the low side in our sample despite having a relatively high MS count. This suggests that there are many other factors which vary according to host environment, physiological and biological conditions that may affect MS and LB counts in the oral cavity. Clinical relevance Our study supports the knowledge that the aetiology of dental caries among older adults is a complex process and it would be wrong to consider caries as a same problem with the same solution for all age groups.